Beneficial reuse of dredged marine soils (DMS) with the inclusion of cement and granular material for engineering applications - Mohammad Zawawi, Rosman; Nurasiah Mira, Anuar; Nurul Syakeera, Nordin; Siti Farhanah, SM Johan; Chan, Chee Ming (Avanti Publishers, 2018)
Plenty of geowaste in Malaysia namely dredged marine soils (DMS) has been increasing over the year. The management of DMS after dredging has become a worldwide problem. Conventionally, the materials are disposed back to the sea. As the minimization of the dredged material during dredging is impossible, extensive work has been done by researchers to develop various economical and viable solutions, such as beneficial reuse of DMS. Series of onedimensional test by using oedometer were tested on DMS with the inclusion cement and mining sand. Based from the results, the cement- and sand-treated DMS have resulted with low settlement reduction, thus increase its effective yield stress and improve its compressibility. As conclusion, it is suggested that DMS can be beneficially reuse for engineering application such as land reclamation or backfills.